2013
DOI: 10.1103/physreve.88.062402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial height on the steady-state persistence probability of linear growth models

Abstract: The effects of the initial height on the temporal persistence probability of steady-state height fluctuations in up-down symmetric linear models of surface growth are investigated. We study the (1+1)-dimensional Family model and the (1+1)- and (2+1)-dimensional larger curvature (LC) model. Both the Family and LC models have up-down symmetry, so the positive and negative persistence probabilities in the steady state, averaged over all values of the initial height h(0), are equal to each other. However, these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…The persistence probabilities of a specific h 0 , P ± S (h 0 ,t), are investigated when the strength of fluctuations is of interest. Previous researches [10,12] have found that the function of P ± S (h 0 ,t) are not power-law decay when fluctuations are very weak compared to the saturation width i.e. |h 0 |≪W sat .…”
Section: The Persistence Probabilities and Exponents In The Steady-statementioning
confidence: 95%
See 4 more Smart Citations
“…The persistence probabilities of a specific h 0 , P ± S (h 0 ,t), are investigated when the strength of fluctuations is of interest. Previous researches [10,12] have found that the function of P ± S (h 0 ,t) are not power-law decay when fluctuations are very weak compared to the saturation width i.e. |h 0 |≪W sat .…”
Section: The Persistence Probabilities and Exponents In The Steady-statementioning
confidence: 95%
“…For all discrete growth models, P ± S (t)∝ t -θ ± S , where θ ± S is the persistence exponent which indicates how long the fluctuations last. In up-down symmetric models, θ + S = θ -S [9,[12][13]18]; while in asymmetric models, θ + S ≠ θ -S [9][10]14,18].…”
Section: The Persistence Probabilities and Exponents In The Steady-statementioning
confidence: 99%
See 3 more Smart Citations